CREATING IMMERSIVE LEARNING SPACES: VIRTUAL REALITY TO IMPROVE ENGLISH VOCABULARY ACQUISITION OF THE BAJO TRIBE - Heri Alfian; Muthmainnah Bahri A. Bohang; Rifka Hafidza Hajar; Achmad Afandy; Nur Husnil Khatimah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
For indigenous learners, especially those from the Bajo tribe in Southeast Sulawesi, Indonesia, limited access to real English learning environments continues to be a major obstacle. Virtual reality (VR) and other emerging immersive technologies present intriguing prospects for developing contextualized and captivating language learning experiences that close this gap. The purpose of this study was to create and assess a virtual reality (VR)-based application for learning English vocabulary that was intended for Bajo students in Southeast Sulawesi, Indonesia. The product was developed through phases of needs analysis, design, expert validation, limited trial, and large-scale deployment using a Research and Development (R&D) methodology. Vocabulary mastery tests, observations, teacher and student questionnaires, and expert validation sheets were used to gather data. According to expert validation, the application's pedagogical and technological quality ratings were very eligible. Teachers saw more active classroom participation during VR-based learning, while students reported better enthusiasm and engagement, according to limited experiments. With average scores rising from 40.35 (pretest) to 70.35 (posttest), a 30-point rise, extensive trials involving 20 kids showed notable gains in vocabulary mastery. Additionally, by incorporating Bajo cultural components into the virtual reality setting, the learning experience becomes more relevant and contextual, which improves motivation and retention. These results demonstrate that virtual reality (VR) apps are not only useful for enhancing vocabulary acquisition but also offer inclusive, culturally sensitive solutions to indigenous people who have little access to real-world English-speaking settings. To further develop immersive language learning, further research is advised to increase the sample size, look at long-term impacts, and combine VR with other technologies such as Augmented Reality (AR) and Learning Management Systems (LMS).